ANALYSIS OF TPACK COMPETENCY-BASED LEARNING MEDIA UTILYZED BY SENIOR HIGH SCHOOL BIOLOGY TEACHERS IN EAST PALU - Dewi Tureni; Raya Agni; Rizka Fardha; Abdul Ashari (Lembaga Penelitian Mahasiswa Penalaran UNM, 2023)
This research is a descriptive research using quantitative approach. This research was conducted at Senior High Schools in East Palu in August 2022. The sample of this study consisted of five biology teachers of State Senior High School in East Palu. The instrument used was an open-ended questionnaire that included five dimensions of TPACK. Each TPACK section contains three issues derived from three indicators. With the help of the open-ended questionnaire, the use of TPACK-based learning media by biology teachers can be measured externally and deeply. The results showed that the most used media by biology teachers is technology-based media particularly PowerPoint media. According to the teachers, PowerPoint media is easy to use and develop, and it can support students to interpret the material effectively and practically. Another media used by biology teachers is traditional media utilization where they use media as learning tools. Finally, the teachers employ pictures of laboratory materials as these are easier to find.